Building web applications with .NET Core 2.1 and JavaScript leveraging modern JavaScript frameworks - Japikse, Philip; Grossnicklaus, Kevin; Dewey, Ben (Apress L.P., 2020)
Roll up your sleeves and jump into building web applications using .NET Core 2.1 and the most popular JavaScript frameworks. You will start by building a data access layer using Entity Framework Core, a RESTful service using ASP.NET Core, and then you will build a web application following the MVC pattern, also using ASP.NET Core. The resulting application is an example e-commerce site using the most appropriate capabilities in .NET Core for building a line of business applications. The second half of Building Web Applications with .NET Core 2.1 and JavaScript is dedicated to teaching you how to develop applications on the client with JavaScript, BootStrap, and related tooling such as TypeScript, WebPack, NPM, and more. Each JavaScript framework will build the same UI as the ASP.NET Core web application from the first half of the book, leveraging the same ASP.NET Core RESTful service and Entity Framework Core data access layer. Building the same UI in the different JavaScript frameworks provides the context and knowledge to reasonably compare and contrast the tools. You will: Ramp up quickly on Entity Framework Core and ASP.NET Core Use TypeScript to deliver better JavaScript Manage your JavaScript build process Know how to build UIs with ASP.NET Core MVC, Angular, and React to make better decisions on which technologies to adopt in your projects Conduct an apples-to-apples comparison of ASP.NET Core, Angular, and React This book is for .NET architects, consultants, and developers who want to modernize their skill set. Some understanding of JavaScript and the Web is useful. Phil Japikse is an international speaker, author, Microsoft MVP, ASPInsider, MCSD, PSM II, and PSD, and a passionate member of the developer community. Currently, he is Director of Consulting and Chief Architect for a consultancy that services medium to large firms. He volunteers as the president for the Cincinnati .NET User Group and the Cincinnati Software Architect Group, he founded the CincyD eliver conference, and he never tires when it comes to learning technology and improving his craft. Follow him on his blog at skimedic.com or Twitter skimedic. Kevin Grossnicklaus is owner of ArchitectNow, a software development firm based in St. Louis, Missouri that he founded in 2009. He got his start developing with Visual Studio and managed .NET code during the early beta cycles in 2001. At ArchitectNow he and his team specialize in a wide variety of tools while delivering applications across a variety of cloud and mobile platforms. Ben Dewey is Creative Director at Tallan, Inc., where he advises companies about their web- and cloud-based technologies. He is a former Microsoft MVP, and published author with more than 18 years of experience writing applications. When not consulting, he is busy training, mentoring, and speaking at conferences and community events. Find him on Twitter @bendewey, StackOverflow, GitHub, or on his blog at bendewey.com.
Print version record
Keywords: Microsoft .NET Framework; Microsoft Visual studio; Web applications; JavaScript (Computer program language); Applications Web; JavaScript (Langage de programmation)